Syndromic treatment of gonococcal and chlamydial infections in women seeking primary care for the genital discharge syndrome: decision-making - Behets Frieda M-T.F; Miller William C.; Cohen Myron S. (The World Health Organization, 2001)
The syndromic treatment of gonococcal and chlamydial infections in women seeking primary care in clinics where resources are scarce, as recommended by WHO and implemented in many developing countries, necessitates a balance to be struck between overtreatment and undertreatment. The present paper identifies factors that are relevant to the selection of specific strategies for syndromic treatment in the above circumstances. Among them are the general aspects of decision-making and caveats concerning the rational decision-making approach. The positive and negative implications are outlined of providing or withholding treatment following a specific algorithm with a given accuracy to detect infection, i.e. sensitivity, specificity and predictive values. Other decision-making considerations that are identified are related to implementation and include the stability of risk factors with regard to time, space and the implementer, acceptability by stakeholders, and environmental constraints. There is a need to consider empirically developed treatment algorithms as a basis for policy discourse, to be evaluated together with the evidence, alternatives and arguments by the stakeholders.